Use of “Privatization”: A Socioeconomic Point of View - Abdullah Murat Tuncer (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
The main goals of privatization are to increase production efficiency, which leads to faster economic growth and development, strengthen the private sector’s role in job creation, improve the public sector’s financial health, and provide free resources for use in public-interest sectors such as education, security, health, housing, transportation, and other infrastructure development initiatives. Privatization has become much more common as a result of globalisation. Priva- tizations made with the aim of closing the deficit and paying debts may pro- vide a temporary and false state of well-being. How- ever, in privatizations, the primary goals are gradually shifting to the second- ary, with most privatizations aiming to close the public finance deficit. The transfer of institutions, which have been gained over time with public funds and have historical and sociological significance for countries, to the private sector through hasty and unsuitable privatisations creates substantial long-term losses for societies. The privatizations that accelerated in our country in 1980s were mostly carried out to close the public finance deficit, and at this point, the debts increased, even more, efficient institutions were lost, and public losses emerged. Most of the projects carried out under pub- lic-private partnerships, which should be considered a form of privatization, have cost the public much more than their real values. As a result, when the privatizations were viewed broadly, the total cost to the public was greater than the profit.